2012
DOI: 10.6088/ijcser.00202030016
|View full text |Cite
|
Sign up to set email alerts
|

Plant characteristics, growth and leaf gel yield of Aloe barbadensis milleras affected by cyanopith biofertilizer in pot culture

Abstract: Biofertilizers are eco friendly and are now most, necessary to support developing organic agriculture and sustainable agriculture. They can provide to the small and marginal farmers an ecofriendly viable weapon to attain the ultimate goal of increasing crop productivity. Cyanobacteria also called blue green algae which are useful to mankind in various ways and constitute a vast potential resource in varied application such as food, feed, fuel, fertilizer, medicine, industrial products and in combating pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The effect of the algal extract may also contribute to the increase in the activity of the main hydrolytic enzymes necessary for seed germination. Similar findings were attained by Moorthy and Malliga, and [52] on Aloe barbadensis. In this regard, Gupta and Shukla [53] indicated that an increase in leaf area ratio and net assimilation rate may be responsible for the stimulatory effect of cyanobacterial biofertilizers on relative growth rate.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of the algal extract may also contribute to the increase in the activity of the main hydrolytic enzymes necessary for seed germination. Similar findings were attained by Moorthy and Malliga, and [52] on Aloe barbadensis. In this regard, Gupta and Shukla [53] indicated that an increase in leaf area ratio and net assimilation rate may be responsible for the stimulatory effect of cyanobacterial biofertilizers on relative growth rate.…”
Section: Discussionsupporting
confidence: 89%